We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
258
3
avatar+404 

The positive difference between two consecutive perfect squares is 59. What is the greater of the two perfect squares?

 Feb 8, 2019
 #1
avatar+2344 
+1

Hello, APatel!

 

A perfect square is the product of a whole number multiplied by itself. Below is a list of the first few perfect squares, in order.

 

x x^2
1 1
2 4
3 9
4 16
5 25
6 36
7 49
8 64
9 81

 

Let equal a positive integer. Let x^2 equal any perfect square. 

Let x+1 equal the subsequent positive integer. Let (x+1)^2 equal the next perfect square.

 

Notice how this is very similar to how I generated consecutive perfect squares in the table; I incremented the "x" column by 1 and squared the result. Also, notice that the question asks for the positive difference of the perfect squares. \((x+1)^2>x^2\) because (x+1)^2 represents the next perfect square. Therefore, it is possible to generate the following equation for this problem:
 

\((x+1)^2-x^2=59\) Expand the binomial.
\(x^2+2x+1-x^2=59\) Look at that! The quadratic terms cancel out, and we are left with quite a basic equation.
\(2x+1=59\) Now, subtract one on both sides.
\(2x=58\) Divide by 2 on both sides.
\(x=29\)  
   

 

We are not done yet! Remember, our goal is to find the greater of the perfect squares. Of course, in this problem, I let (x+1)^2 represent the larger one.

 

\(x=29\\ (x+1)^2\) Substitute 29 into this expression and simplify accordingly. 
\((29+1)^2\)  
\(30^2\)  
\(900\) This is the larger of the 2 perfect squares. 
   


 

 Feb 8, 2019
 #2
avatar+6045 
+1

\(\text{let }a>b\\ a^2-b^2 = 59\\ (a+b)(a-b)=59\\ \text{The only factors of 59 are 1 and 59}\\ (a+b)=59\\ (a-b)=1\\ 2a=60\\ a=30\\ b=29\\(30)^2=900 \text{ is the larger of the two squares}\)

.
 Feb 8, 2019
edited by Rom  Feb 8, 2019
 #3
avatar+19813 
+1

A lot of times, you can eliminate a step by assigning 'x' the value you are looking for....

 

x = larger number

x-1 = the previous number

 

The difference in these squares = 59

 

x^2 - (x-1)^2 = 59     expand

x^2 - x^2 + 2x -1 = 59

2x-1 = 59

2x = 60

x = larger number = 30         x^2 = 900

 Feb 8, 2019

18 Online Users

avatar